2000
DOI: 10.1074/jbc.m006964200
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition by Insulin-like Growth Factor-binding Protein-3 in T47D Breast Cancer Cells Requires Transforming Growth Factor-β (TGF-β) and the Type II TGF-β Receptor

Abstract: This study explores the relationship between anti-proliferative signaling by transforming growth factor-␤ (TGF-␤) and insulin-like growth factor-binding protein-3 (IGFBP-3) in human breast cancer cells. In MCF-7 cells, the expression of recombinant IGFBP-3 inhibited proliferation and sensitized the cells to further inhibition by TGF-␤1. To investigate the mechanism, we used T47D cells that lack type II TGF-␤ receptor (TGF-␤RII) and are insensitive to TGF-␤1. After introducing the TGF-␤RII by transfection, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 56 publications
4
89
2
Order By: Relevance
“…Most interestingly, these studies suggest that the T␤RI is not responsible for the EGF-induced Smad phosphorylation, since it is evident in R1B cells, which lack the type I receptor. Additionally, IGFBP-3 is a further biological mediator, which is capable to stimulate Smad2 and Smad3 phosphorylation and moreover to potentiate TGF-␤-induced Smad activation (21,23). However, in contrast to the EGF-induced Smad activation, these studies indicate that IGFBP-3 signaling in T47D and MCF-7 breast cancer cells activates T␤RI and that this requires the presence of T␤RII.…”
Section: Figmentioning
confidence: 88%
See 1 more Smart Citation
“…Most interestingly, these studies suggest that the T␤RI is not responsible for the EGF-induced Smad phosphorylation, since it is evident in R1B cells, which lack the type I receptor. Additionally, IGFBP-3 is a further biological mediator, which is capable to stimulate Smad2 and Smad3 phosphorylation and moreover to potentiate TGF-␤-induced Smad activation (21,23). However, in contrast to the EGF-induced Smad activation, these studies indicate that IGFBP-3 signaling in T47D and MCF-7 breast cancer cells activates T␤RI and that this requires the presence of T␤RII.…”
Section: Figmentioning
confidence: 88%
“…Thus, it has been reported that the insulin-like growth factor binding protein-3 (IGFBP-3) can stimulate Smad2 and Smad3 phosphorylation. Although this activation occurs in the absence of endogenous or exogenous TGF-␤, it requires the T␤RII, implying an interaction between IGFBP receptors and TGF-␤ receptors (21)(22)(23). S1P receptors are also known to cross-communicate with other GPCRs as well as other plasma membrane receptors, including receptor-tyrosine kinases (24 -26).…”
mentioning
confidence: 99%
“…In cells transfected to express TGF-␤ receptor type II, insulin-like growth factor binding protein-3 (IGFBP-3) stimulated Smad2 and Smad3 phosphorylation, potentiated TGF-␤1-stimulated Smad phosphorylation, and cooperated with exogenous TGF-␤1 in cell growth inhibition. 30 In PC12 cells, nerve growth factor led to activation of the Smad pathway independent of TGF-␤. 31 Advanced glycation end products caused rapid Smad2/3 activation in renal and vascular cells that was independent of TGF-␤, 32 suggesting the importance of Smad pathway in diabetic organ injury.…”
Section: Discussionmentioning
confidence: 99%
“…In T47D breast cancer cells, that lack TβRII, restoration of this receptor by transfection sensitized the cells to Smad2 and Smad3 phosphorylation, and inhibition of cell proliferation, by IGFBP-3 (Fanayan, et al 2000). TβRI was also phosphorylated in response to IGFBP-3, suggesting that IGFBP-3 required an intact TGFβ signaling pathway for growth inhibition of this cell line (Fanayan, et al 2002).…”
Section: Lrp1 and Tgfβ Signalingmentioning
confidence: 95%